Kid's Box [sound recordig] - Nixon, Caroline; Tomlinson, Michael (London Cambridge University Press, 2008)
Kid's Box is bursting with bright ideas to inspire you and your pupils! This six-level course gives children a confident start to learning English, and makes lessons a joy for teachers. Perfect for general use, Kid's Box also fully covers the syllabus of the Cambridge Young Learners English (YLE) tests. New language is presented through amusing stories that your students will adore and practised with fantastic songs and activities, making the learning process a delight. Key language is continuously revised and recycled, helping to build children's confidence, and a focus on communicative activities ensures that children use the language they have learned in a fun, 'no-pressure' context. The loveable members of the Star family will delight young learners, while an extensive range of supplementary materials provides the teacher with all the extra activities they need
Audio CD
1
Keywords: Educational Videos; English Learning; CD.ROM (Children); Children Multimedia